(untitled) (Journal of the College of Basic Education, 2026)
The research aims to develop an instructional strategy based on Experiential Learning Theory and to identify its effect on students’ achievement in the subject of Art Analysis and Criticism at the Institute of Fine Arts. The research population consisted of fifth-grade morning-study students in boys’ Institutes of Fine Arts in Iraq, totaling (973) students. To achieve the research objectives, the researcher adopted the experimental method and selected a sample of (40) fifth-grade students from the Institute of Fine Arts, who were divided into two groups. Several statistical methods were utilized, and the results revealed the following: There were statistically significant differences between the mean scores of the experimental and control groups in the achievement test in favor of the experimental group. The calculated t-value was (6.90) compared to the tabulated value of (2.02), indicating a large effect size of (1.87). There were statistically significant differences between the pre- and post-achievement test scores of the experimental group in favor of the post-test. The calculated t-value reached (7.36) compared to the tabulated value of (2.09), reflecting a large effect size of (2.21). The study presented several recommendations, most notably: Adopting the Experiential Critical Journey Strategy as one of the primary strategies for teaching Art Analysis and Criticism in Iraqi Institutes of Fine Arts. Integrating the strategy into teaching plans for other art subjects due to its proven impact on achievement. To complement the research procedures, the researcher suggests conducting further studies, including: The effect of the Experiential Critical Journey Strategy on other art subjects such as art appreciation, design, and art history. The effect of the strategy on developing artistic creativity and innovation skills among Fine Arts students.